Study of immune alterations in patients with chronic fatigue syndrome with different etiologies - Racciatti, D; Dalessandro, M; Delle Donne, L; Falasca, K; Zingariello, P; Paganelli, R; Pizzigallo, E; Vecchiet, J (International journal of immunopathology and pharmacology, 2004)
The Chronic Fatigue Syndrome (CFS) is characterized by symptoms lasting for at least six months and accompanied by disabling fatigue. The etiology of CFS is still unclear. At the National Center for Study of the Infectious Diseases Department of the Chieti University some immune investigations were performed with the purpose of detecting markers of the disease. CD4+, CD8+, NK CD56+ and B CD19+ lymphocytes were studied in 92 male and 47 female patients and in 36 control subjects. CFS patients were divided in three groups with a post-infectious onset (PI-CFS), an non post-infectious onset (NPI-CFS) and a non post-infectious onset with associated infections (NPI-CFS + AI). Both CD4+ and CD8+ lymphocytes were reduced in the CFS patients. However, the CD4+/CD8+ ratio was increased in the CFS patients without difference between males and females. CD56+ cells of CFS patients were also reduced. In particular, blood CD56+ cells counts were significantly higher in PI-CFS patients than in the NPI-CFS subjects. These data confirm our preliminary results suggesting a key-role of a dysfunction of the immune system as a precipitating and-or perpetuating factor of the syndrome.